Pregnant Mother's Consumes Fe Tablets and Anemia in Palu City - Pont, Anna Veronica; Lisnawati, Lisnawati (Poltekkes Kemenkes Palu, 2020)
The World Health Organization (WHO) estimates that around 10% of live births experience complications from postpartum bleeding. The most frequent complication of postpartum bleeding is anemia. The purpose of this study was to determine the relationship of compliance of pregnant women consuming Fe tablets with anemia in the Talise Health Center Community in Palu City. This type of research was a cross-sectional design that involved first and second-semester pregnant women, and as many as 209 people. The number of samples was 34 people. Purposive sampling technique. Univariate and bivariate analysis (chi-square test). The results showed 92.3% of respondents' compliance and 7.7% of anemia, while non-compliant respondents took 37.5% of Fe tablets without anemia, and 62.5% of those who were not obedient and had anemia. Chi-square test results p = 0.004 (<0.05), there was an effect of compliance of pregnant women with anemia in Talise Health Center Community, Palu City. In conclusion, there is an influence of compliance of pregnant women with anemia at the Talise Health Center Community in Palu City. It is recommended to actively conduct counseling about the benefits of Fe tablets during the pregnancy.